RECLAIMING INDONESIAN-NESS: ONLINE-OFFLINE ENGAGEMENT OF INDONESIAN EXILES IN NETHERLANDS - Ibnu Nadzir (Masyarakat Indonesia, 2018)
This article explores online-offline engagements of Indonesian exiles in Netherlands. By looking into their internet practices, this article affirms the notion that it is essential for Internet research to comprehend social and cultural practices engaged in both space as an entanglement. To elaborate the argument, this article analyzed two important cases where the online-offline engagements are performed by Indonesian exiles, which are: IPT 1965 events and Diskusi Forum. Since the social and cultural practices were performed online and offline, this research is also conducted in both spaces simultaneously.  The research itself was initiated  from two main questions: First, how do Indonesian exiles employed online-offline engagement to mobilize their cause? Second, how do their offline-online engagement affect their existence as a displaced community? The article then argues that the engagement enacted by Indonesian exiles is performed fluidly in online-offline spaces. In consequence, events and practices in both arenas are influential to one another. Moreover, borrowing the framework of Jackson (2013) on storytelling, this article shows that the offline-online engagements  has enabled Indonesian exiles to reclaim the sense of being Indonesian.